Clinical Impact of Primary Tumor Location in Metastatic Colorectal Cancer Patients Under Later-Line Regorafenib or Trifluridine/Tipiracil Treatment - Nakajima, Hiromichi; Fukuoka, Shota; Masuishi, Toshiki; Takashima, Atsuo; Kumekawa, Yosuke; Kajiwara, Takeshi; Yamazaki, Kentaro; Negoro, Yuji; Komoda, Masato; Makiyama, Akitaka; Denda, Tadamichi; Hatachi, Yukimasa; et al. (Frontiers in Oncology, 2021)
Background: Primary tumor location (PTL) is an important prognostic and predictive factor in the first-line treatment of metastatic colorectal cancer (mCRC). Although regorafenib (REG) and trifluridine/tipiracil (FTD/TPI) have been introduced recently, the clinical impact of PTL in these treatments is not well understood. Materials and Methods: We retrospectively evaluated patients with mCRC who were registered in a multicenter observational study (the REGOTAS study). The main inclusion criteria were Eastern Cooperative Oncology Group performance status (ECOG PS) of 0–2, refractory or intolerant to fluoropyrimidines, oxaliplatin, irinotecan, angiogenesis inhibitors, anti-epidermal growth factor receptor therapy (if RAS wild-type), and no prior use of REG and FTD/TPI. The impact of PTL on overall survival (OS) was evaluated using Cox proportional hazard models based on baseline characteristics. Results: A total of 550 patients (223 patients in the REG group and 327 patients in the FTD/TPI group) were included in this study, with 122 patients with right-sided tumors and 428 patients with left-sided tumors. Although the right-sided patients had significantly shorter OS compared with the left-sided patients by univariate analysis (p = 0.041), a multivariate analysis revealed that PTL was not an independent prognostic factor (hazard ratio, 0.95; p = 0.64). In a subgroup analysis, the OS was comparable between the REG and FTD/TPI groups regardless of PTL (p for interactions = 0.60). Conclusions: In the present study, PTL is not a prognostic and predictive factor in patients with mCRC under later-line REG or FTD/TPI therapy.